Myocardial perfusion and oxygenation are impaired during stress in severe aortic stenosis and correlate with impaired energetics and subclinical left ventricular dysfunction. - Mahmod, M; Francis, J; Pal, N; Lewis, A; Dass, S; De Silva, R; Petrou, M; Sayeed, R; Westaby, S; Robson, M; Ashrafian, H; Neubauer, S; et al. (2014)
BACKGROUND: Left ventricular (LV) hypertrophy in aortic stenosis (AS) is characterized by reduced myocardial perfusion reserve due to coronary microvascular dysfunction. However, whether this hypoperfusion leads to tissue deoxygenation is unknown. We aimed to assess myocardial oxygenation in severe AS without obstructive coronary artery disease, and to investigate its association with myocardial energetics and function. METHODS: Twenty-eight patients with isolated severe AS and 15 controls underwent cardiovascular magnetic resonance (CMR) for assessment of perfusion (myocardial perfusion reserve index-MPRI) and oxygenation (blood-oxygen level dependent-BOLD signal intensity-SI change) during adenosine stress. LV circumferential strain and phosphocreatine/adenosine triphosphate (PCr/ATP) ratios were assessed using tagging CMR and 31P MR spectroscopy, respectively. RESULTS: AS patients had reduced MPRI (1.1 ± 0.3 vs. controls 1.7 ± 0.3, p < 0.001) and BOLD SI change during stress (5.1 ± 8.9% vs. controls 18.2 ± 10.1%, p = 0.001), as well as reduced PCr/ATP (1.45 ± 0.21 vs. 2.00 ± 0.25, p < 0.001) and LV strain (-16.4 ± 2.7% vs. controls -21.3 ± 1.9%, p < 0.001). Both perfusion reserve and oxygenation showed positive correlations with energetics and LV strain. Furthermore, impaired energetics correlated with reduced strain. Eight months post aortic valve replacement (AVR) (n = 14), perfusion (MPRI 1.6 ± 0.5), oxygenation (BOLD SI change 15.6 ± 7.0%), energetics (PCr/ATP 1.86 ± 0.48) and circumferential strain (-19.4 ± 2.5%) improved significantly. CONCLUSIONS: Severe AS is characterized by impaired perfusion reserve and oxygenation which are related to the degree of derangement in energetics and associated LV dysfunction. These changes are reversible on relief of pressure overload and hypertrophy regression. Strategies aimed at improving oxygen demand-supply balance to preserve myocardial energetics and LV function are promising future therapies.